The sociology of health & illness : critical perspectives - Conrad, Peter (Worth, 2005)
This collection of 49 readings offers an integrated analysis of the most important issues regarding health and health care from a critical and sociological perspective. Substantive introductions provide context for the readings. With ten new and two revised essays, the Seventh Edition contains more coverage of key areas such as alternative medicine, the pharmaceutical industry, and the relationship between healthcare and politics.
Keywords: Sociology, Medical; sociologie; sociální lékařství; Socioeconomic Factors; socioekonomické faktory; lékařská sociologie; statistika, zdravotnická statistika